2018
DOI: 10.1097/nur.0000000000000373
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the Clinical Nurse Specialist From Other Graduate Nursing Roles

Abstract: Healthcare providers must be aware of the differences in graduate nursing roles, especially in comparing the CNS with other roles to avoid confusion that may lead to roles being underused with a limited job scope. The CNS provides a unique set of services at all system outcome levels and is an essential part of the healthcare team especially in the acute care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 12 publications
1
45
0
5
Order By: Relevance
“…This is at the core of a sense of belonging as this increases mutual trust and therefore respect, wellbeing and self-esteem. The impact of working conditions such as remuneration, workload allocation, staffing levels and lack of role clarity [75] have been raised previously as well as in this study [31, 33, 72, 73]. The impact of workload and the working environment on the personal self has also been documented previously [76, 77].…”
Section: Discussionsupporting
confidence: 73%
“…This is at the core of a sense of belonging as this increases mutual trust and therefore respect, wellbeing and self-esteem. The impact of working conditions such as remuneration, workload allocation, staffing levels and lack of role clarity [75] have been raised previously as well as in this study [31, 33, 72, 73]. The impact of workload and the working environment on the personal self has also been documented previously [76, 77].…”
Section: Discussionsupporting
confidence: 73%
“…Overall, the finding of a four-competency-factor solution reflects similarities in the US and Canadian CNS competencies. The US CNS competencies are grouped under three spheres of patient, nursing and organisation (Baldwin et al, 2007) other specialty practitioners such as nurse administrators work in this sphere (Hanson & Hamric, 2003), the CNS practice within the organisation is supported by the other complimentary competence areas of patient, clinical nursing leadership and scholarship, which enable them to influence the organisational outcomes in the micro-, meso-and macrosystem (Mayo et al, 2017;Mohr & Coke, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed several, even hundreds, of job titles in use (Leary, Maclaine, Trevatt, Radford, & Punshon, 2017;Pulcini, Jelic, Gul, & Loke, 2010). The array of titles used is found a problematic issue in several countries across Europe causing disparity and confusion (Dury et al, 2014;Leary et al, 2017;Maier et al, 2017;Mohr & Coke, 2018). Recently, some organizations have begun to develop frameworks for APN; however, there is a paucity of information guiding the policymaking or practice implementation process (Chang, Gardner, Duffield, & Ramis, 2012;Schober, Gerrish, & McDonnell, 2016).…”
Section: Introductionmentioning
confidence: 99%